2010
DOI: 10.1007/s12206-010-0625-8
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated heat transfer and temperature distributions in a gas turbine combustion liner under base-load operation

Abstract: Prediction of temperature distributions on hot components is important in development of a gas turbine combustion liner. The present study investigated conjugated heat transfer to obtain temperature distributions in a combustion liner with six combustion nozzles. 3D-numerical simulations using FVM commercial codes, Fluent and CFX were performed to calculate combustion and heat transfer distributions. The temperature distributions in the combustor liner were calculated by conjugation of conduction and convectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…3(a) shows the distributions of von Mises equivalent stress on the surface of the combustion liner substrate. The highest stress is locally induced at the inlet of the rib-roughened region that exactly matches the highest temperature region [19]. Ó2010 Journal of Mechanical Science and Technology).…”
Section: Review Of the Previous Workmentioning
confidence: 82%
See 2 more Smart Citations
“…3(a) shows the distributions of von Mises equivalent stress on the surface of the combustion liner substrate. The highest stress is locally induced at the inlet of the rib-roughened region that exactly matches the highest temperature region [19]. Ó2010 Journal of Mechanical Science and Technology).…”
Section: Review Of the Previous Workmentioning
confidence: 82%
“…The boundary conditions for calculating the thermal stress and strain distributions, such as substrate temperature distributions and environment gas temperature are adopted from our previous work [19].…”
Section: Thermal Stress Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, if an operation condition is unsuitable, local thermal cracks and structural failure may occur due to the high thermal stress. Therefore, a thermal analysis [9][10][11] and a failure analysis [12][13][14][15][16] are required for an effective thermal design.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [9] investigated the heat transfer and temperature by using a rib-roughened surface and an impinging jet cooling system in an actual combustion liner. They found that the temperature distributions are induced by the attachment and mixing of high temperature flow from combustor nozzles.…”
Section: Introductionmentioning
confidence: 99%